Pengaruh Sistem Pengendalian Akuntansi Terhadap Kinerja Manajerial dengan Menggunakan Ketidakpastian Lingkungan sebagai Variabel Moderating pada PT Asia Sawit Lestari di Batang Hari - Rian Fitra Apriandi (JURNAL RISET AKUNTANSI JAMBI, 2021)
This study aims to: (1) determine the effect of accounting control systems on managerial performance (2) to determine whether environmental uncertainty can influence the relationship memodreasi accounting control system on managerial performance. This study is a survey by distributing questionnaires directly to the sample. Samples taken total 15 samples were taken based on the existing population of this study is that the study population (census). Analysis using simple linear regression analysis. Results of this study indicate that (1) the accounting control system has positive influence on managerial performance (2) negative influence environmental uncertainty or could not moderate the relationship between accounting control systems on managerial performance.